2006
DOI: 10.1002/chem.200500971
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Catalytic‐Hydrogenation Behavior of SiO2‐Embedded Nanoscopic Pd, Au, and Pd–Au Alloy Colloids

Abstract: Colloids embedded in a silica sol-gel matrix were prepared by using fully alloyed Pd-Au colloids, and pure Pd and Au colloids stabilized with tetraalkylammonium bromide following a modified sol-gel procedure with tetrahydrofuran (THF) as the solvent. Tetraethoxysilicate (TEOS) was used as the precursor for the silica support. The molar composition of the sol was TEOS/THF/H2O/HCl = 1:3.5:4:0.05 for the bimetallic Pd-Au and TEOS/THF/H2O/HCl = 1:4.5:4:0.02 for Pd and Au monometallic systems. After refluxing, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 89 publications
1
63
0
Order By: Relevance
“…The monometallic Au catalyst displayed very low activity in the selective semi-hydrogenation of 3-hexyn-1-ol, whereas the bimetallic Au-Pd catalyst exhibited high activity and was remarkably resistant to deactivation. Some years later, Parvulescu et al [171] evaluated the catalytic activity of the before mentioned catalysts in the selective hydrogenation of 3-hexyn-1-ol, cinnamaldehyde, and styrene. Their results showed that alloying Pd with Au in bimetallic colloids led to enhanced activity and improved selectivity.…”
Section: Synthesis By Dispersion Of Gold Colloids or Presynthesized Amentioning
confidence: 99%
“…The monometallic Au catalyst displayed very low activity in the selective semi-hydrogenation of 3-hexyn-1-ol, whereas the bimetallic Au-Pd catalyst exhibited high activity and was remarkably resistant to deactivation. Some years later, Parvulescu et al [171] evaluated the catalytic activity of the before mentioned catalysts in the selective hydrogenation of 3-hexyn-1-ol, cinnamaldehyde, and styrene. Their results showed that alloying Pd with Au in bimetallic colloids led to enhanced activity and improved selectivity.…”
Section: Synthesis By Dispersion Of Gold Colloids or Presynthesized Amentioning
confidence: 99%
“…Gold is very useful as an alloying metal and it has been used with metal such as palladium [1][2][3][6][7][8][9][10][11][12][13] and platinum [7,10,[14][15][16] for various catalytic reactions. The interest for Au-Pd catalysts has been improved in recent years, as they were found to be superior to pure Pd and Au supported catalysts in various reactions as hydrogenation [17], hydrodechlorination [18,19] and hydrodesulphuration [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts to incorporate metal colloids into a solid matrix have been presented in the literature. [12] However, reports about embedding Pt colloids are scarce, and those available primarily refer to polymeric matrices. [13] To verify the effect of the Pt particle size, these catalysts were tested in the reduction of NO with isopentane.…”
Section: Introductionmentioning
confidence: 99%